Treating liquid expulsion in children with feeding disorders. Issue 1 (8th January 2018) - Shalev, Rebecca A.; Milnes, Suzanne M.; Piazza, Cathleen C.; Kozisek, Jennifer M.
Abstract : In the current investigation, we compared and evaluated the effects of two intervention procedures, a modified chin prompt and reclined seating, on the liquid expulsion of 2 children with feeding disorders. For both participants, expulsion decreased to clinically meaningful levels when we added the modified chin prompt or reclined seating to a treatment package consisting of differential reinforcement of acceptance, nonremoval of the cup, and re‐presentation. We discuss possible mechanisms underlying the effects of the 2 interventions and areas for future research.